The Changing Structure of Mass Housing Development in Istanbul - Senem Kozaman Som; Betul Sengezer; Ayse Nur Okten (European Regional Science Association (ERSA), 2010)
In Istanbul, especially after 1980s, economic and social policies are the major axis that constitutes the development dynamics of the metropol. The urban sprawl began with the rapid urbanization process and has continued with the increasing concentration caused by individual housing solutions and changes in real estate development policies. In this period, although planning attributes an increased importance, the spatial character of the period can be determined as the excessive concentration in built up area and low density expansion in the periphery of Istanbul. During this period, - However, due to the implementations of the plans there emerged a structure, where the local plans constantly underwent revisions and amendments, - Furthermore, in contrast to the preparation of broad scale plans, the development of housing is directed by projects that independent from the plans. - Until 1990s, the public lands are used as a tool for creating healthier city, but in 2000s public lands are seen as the tools that provides annuity. These are the examples of changing paradigms and problems in the housing development. With the changing socio-economic and technological conditions housing preserve its characteristic of being a major cumulative problem. In this context, current developments such as "urban renaissance", "smart growth" approaches are defined as the main principles of the new housing development process in 1990s. However from the mid-2000s, the experiences based on these trends, are questioned with highlighting the 'urban capacity' contradictions. After 1990 public- private sector partnerships or only private sector has begun to develop mass housing projects in Istanbul. These projects are high-density projects, furthermore structuring conditions of the projects are against to construction regulations and the equipment standards (education, health facilities and green space) are ignored. From the Istanbul example, with its spatial heritage and different planning culture from most of the developed countries, the subject of this paper is to review this fundamental problem with reflecting the changing concept in public and mass housing approaches. These problems and concerns are exposed with spatial schemes and based on housing and population statistics in Istanbul.
Keywords: 330